The Publicness Paradox: Young People And The Production Of Parochial Places - De Backer, Mattias (Environnement urbain, 2016)
Many assumptions underlie a concept such as public space but seldom are they made explicit in the public debate. In this paper I will investigate what constitutes ‘publicness’ by building on research with young people hanging out in public space in Brussels. I will argue that young people, by meeting in public space, produce parochial places (Lofland, 1998). By doing so they transgress certain rules in public space. I will argue that the paradox embedded in ‘publicness’ is that in order for young people to truly be in public they have to break or bend the rules of that public; a person can only be in space when that space becomes of that person. The question then becomes if these forms of parochiality allow us to overcome the boundaries between people and communities, and between public and private.